(untitled) (Al-Academy, 2021)
The results of previous scientific studies showed that knowledge is something and application is something else, that’s why teachers’ preparation programs focused, in the present time, on special standards for knowledge and performance, i.e., who has knowledge is not necessary able to apply it in his life or in his field of work, which led to the existence of a gap between knowledge and application. Based on that, those interested in (teachers’ preparation) reconsidered their work evaluation, thus the concept of competency appeared at the end of the sixties of the past century to address the negative in teachers’ preparation. The following contains a number of competency features in teachers’ preparation programs: Teachers’ effectiveness and abilities in performing their work, practicing teaching is considered a standard for success, increasing the trainees’ experiences)The current study aims to define the effect of teaching competencies required in enhancing self-confidence for the arts education students during the application, and in order to achieve the study objective, the researcher derived the following null hypothesis: There is no statistically significant difference at the level (0.05) of significance in self-confidence scale degrees between the experimental group that studied the competencies and the control group that relied on theoretical lectures in the subject of observation, application and teaching methodologies The two groups have been equalized, and the researcher prepared a form for the teaching competency and self-confidence scale and they were subject to validity and reliability through using the appropriate statistical means. The results showed the superiority of the experimental group over the control group in self-confidence scale. The researcher set forth a number of recommendations and suggestions.